A Case study of medicinal plants used by local women for gynecological disorders in Karaikal (U.T. of Puducherry) - Shukla, Manisha; Rashiya Begum, Y; Mishra, Manoj (Journal of Phytology, 2012)
Indigenous knowledge is a potential tool in searching for new economic plants for uses of medicinal plants for various purposes. The present paper deals with the indigenous medicinal plants used by the local women of karaikal district .The rural women depend on the herbal medicines for curing various gynecological disorders. They do not approach the physicians due to lack of awareness, shyness or hesitation. Therefore a survey was conducted on medicinal plant species used to manage gynecological disorders at karaikal. The present work is based on the results of observations and semi-structured interviews conducted on traditional uses of some plants by the local women .The locals especially women of the area have been using the medicinal plants for many day to day uses for various ailments and are dependent on the plants in their surroundings for food, health, medication and various cultural purposes. A total of 44 important plants belonging to 27 families were recorded which were used medicinally and various other purposes by the local women. People have strong faith in herbal medication and women are leading the men in applying the recipe for medication by these plants. About 125 informants were interviewed in this regard.